HISTORY OF THE DEVELOPMENT OF THE PROBLEM OF TEACHING AND MORAL UPBRINGING UNITY - Марія Данюк; Вікторія Бак (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
In the article the problem of the expediency of combining pupils' learning and moral upbringing has been considered as one of the ways of humanitarization of science education. There have been analyzed its historical roots in order to reveal the means of bridging the gap between knowledge of nature and human beings through interaction of learning activity subjects. This idea is represented in the pedagogical system of humanistic direction, and is in particular reflected in works of D. Andreyev, K. Venttsel, Ya. Komenskyi, M. Neplyuyev, M. Pyrohov, H. Skovoroda, R. Tahor, L. Tolstoy, K. Ushynskyi, A. Shveytser, P. Yurkevychs. There have been determined the main feature of Humanism of 18th-20th centuries - spiritual anthropocentrism, according to which human highest spiritual principle was accepted. At the same time moral core in learning was considered to be opposed to its subject specialization.